Pararasbora moltrechti Regan, 1908, a senior synonym of Aphyocypris amnis Liao et al., 2011 (Teleostei: Cyprinidae) in Taiwan with morphological and molecular evidence - Yeh, Ming-Fon; Jang-Liaw, Nian-Hong; Chang, Shih-Tsang; Han, Chiao-Chuan; Ho, Lin- Tai; Wang, Shen-Chih (Zootaxa, 2024)
The endemic cyprinid, Pararasbora moltrechti Regan, 1908 is briefly redescribed from central Taiwan. A more detailed description was first provided in Mandarin by Chen & Fang, 1999. A second, rather doubtful description error created a new cyprinid species, Aphyocypris amnis Liao et al., 2011, which is almost identical to the original species. The new species was found in a small tributary of the Jushuei River basin, just 0.5 km from Lake Candidius—Sun Moon Lake, the same location where P. moltrechti was originally found. Chen et al. (2012) clearly noted this synonym in the remarks of the Red Data Fish Book in AGC. The incorrect scientific name was added to the Governmental protection list in AGC, causing further issues for conservation management. Solid evidence, not only from morphological data but also from increasing mtDNA documentation, supports the fact that the later published name is redundant. Mito-genetic results also suggest that they are the same species with no distinct genetic differentiation. Herein we clearly state that the Pararasbora moltrechti Regan, 1908 is the senior synonym of Aphocypris amnis Liao et al., 2011 (Teleostei: Cyprinidae) in Taiwan.